Emergency room nurse competencies: narrative review of the literature (Dissertation Nursing, 2023)
BACKGROUND: Emergency departments are dynamic and unpredictable environments that must ensure timely responses and interventions by addressing urgent emergency situations. The diversity of nurses' roles in different clinical areas leads to developing tools for their context. Competency frameworks make it possible to decline distinctive area competencies and ensure competent and safe care.AIM: To identify the competencies of the Emergency Room nurse in order to define the distinctive ones in this setting through existing frameworks in the literature.METHODS: A narrative review of literature by searching databases and journals. The search was supplemented with secondary resources.RESULTS: Five frameworks were identified from the international literature (FEN; RCN; NENA; CENA; ENA & AAENP). They were analyzed according to nine domains: clinical competence, communication, teamwork, environment and resource, professional development, leadership, legal practice, and professional ethics, research, and quality. No framework of emergency nurse competencies was identified in our country.CONCLUSION: The development of mappings aims to ensure safe and standard practices for professional education. The competencies analyzed within this study vary according to the educational background and the Health Care Systems of different States. The nine domains highlighted the similarities of the mappings that allow for the definition of standards for the emergency urgency nurse.
Keywords: emergency department; emergency room; competencies; framework; nurse